Controlled probe surface chemistry for nanoscale contact deformation - Constantinides, Georgios; Tweedie, Catherine A.; Blackman, Gregory S. (My University, 2007)
Mechanical behavior of polymer thin films and nanocomposites under contact loading is partially controlled by physical confinement and interfacial chemistry'. Although the contact deformation mechanics of amorphous polymers can be investigated very near the surface, it has become increasingly acknowledged that interfacial chemical interactions may play a large role in near-interface mechanical behavior. Therefore, there is a need for nanoscale mechanical testing in which the indenter probe surface chemistry is tunable. Herein, a spherical, nanoindentation probe is fabricated, chemically functionalized, and used to measure the mechanical properties of an amorphous polystyrene surface.
Keywords: Capillarity; Mechanical engineering; Nanostructured materials; Surface chemistry; Surfaces